(3MGTjI Ydi TQM GdJLQjO ddMdjs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3bGd GdeGJf aj JMQjQ eSGFd GdcdGe(B: (3hdGHO ef HjGf JYQja Yde GdcdGe hHjGf GdMGLI Edjg hehVhYg djMUd GdTQhY Ydi HUjQI hEfeG CgedgG GdeUfas
(3BNQgG (B:s
(3BNQgG(B: (3cJbSje GdQbHI Edi GdeDefI hGdaGSbI hcJbSje GdhLhO aEfg HGfVeGe GdeGgjGJ dg dG jUjQ eGgjI fhYjI aEf GdeGgjI aj PGJgG fhYjI hEfeG JhLO HGdhLhOs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds